PEMAHAMAN SISWA KELAS III SD TERHADAP KONSEP PENJUMLAHAN DAN PENGURANGAN MELALUI MEDIA PERMAINAN KARTU MATEMATIKA - Amanda Chindy Rizki Sukronia; Yohamintin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the effectiveness of using mathematical card game media in improving the understanding of addition and subtraction concepts in grade III elementary school students. The method used is a systematic literature review of various studies related to the use of mathematical card media in basic mathematics learning. Data sources in this study are in the form of articles, theses, books, and also scientific papers that are analyzed based on the objectives that have been formulated. The results of the study indicate that mathematical card game media can significantly increase students' involvement, motivation, and understanding of mathematical concepts, as well as develop social skills such as cooperation and communication. However, there are challenges such as the potential for students to focus too much on the game aspect so that the main learning objectives are neglected, as well as differences in students' abilities in understanding the rules of the game. In conclusion, mathematical card game media is an effective learning tool to improve mathematics learning outcomes, especially in addition and subtraction operations, with the note that good management and adequate teacher training are needed to maximize its benefits.